Psykhe (Santiago) 2000
DOI: 10.7764/psykhe.v9i2.20301
|View full text |Cite
|
Sign up to set email alerts
|

Un Programa de Educación para la No-Violencia

Abstract: En el presente artículo se describe el proyecto de investigación e innovación tecnológica "Diseño, implementación y evaluación de un Programa de Educación para la no-violencia". Este proyecto financiado por Fondef (Fondo de fomento al desarrollo científico y tecnológico) se inserta en los Contenidos Transversales de la Educación, propuestos en la Reforma Educacional. El objetivo general es tener un impacto, en el mediano plazo, en: maltrato infantil y abuso intrafamiliar, maltrato y abuso en el contexto escola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…News about school violence contributed to stimulating the interest of teams working within the Ministry of Education, who found that this line of work on school climate provided precise intervention targets and proposals. The projects developed by Aron and her team offered solutions that, in this context, found their specific problem (Aron, 2000; Aron & Milicic, 2000). Since then, the ministry would develop joint attention to school climate (still conceptualized as convivencia ) and violence.…”
Section: School Violence In Chilementioning
confidence: 99%
“…News about school violence contributed to stimulating the interest of teams working within the Ministry of Education, who found that this line of work on school climate provided precise intervention targets and proposals. The projects developed by Aron and her team offered solutions that, in this context, found their specific problem (Aron, 2000; Aron & Milicic, 2000). Since then, the ministry would develop joint attention to school climate (still conceptualized as convivencia ) and violence.…”
Section: School Violence In Chilementioning
confidence: 99%